Massachusetts Business Taxes: Unfair? Inadequate? Uncompetitive? - Robert Tannenwald (Federal Reserve Bank of Boston, 2004)
In debating Massachusetts business tax policy, protagonists have cited many different indicators purporting to assess the fairness, adequacy, and competitiveness of the Commonwealth's business taxes. These statistics actually reveal very little about the degree to which Massachusetts business taxes achieve these widely accepted tax policy goals. The author explains why these indicators are misleading and presents new indicators of business tax competitiveness that, although imperfect, are more accurate than those most widely quoted. The article concludes that the fairness of Massachusetts business taxes is unclear and that the Commonwealth's corporate income taxes are inadequate. The clearest conclusion drawn is that Massachusetts business taxes do not harm its competitive standing.
Keywords: O10; H71; H25; 330; Unternehmensbesteuerung; Steuergerechtigkeit; Steuerwettbewerb; Massachusetts